Genetic diversity of murine norovirus populations less susceptible to chlorine - Wanguyun, Aken Puti; Oishi, Wakana; Rachmadi, Andri Taruna; Katayama, Kazuhiko; Sano, Daisuke (Frontiers in Microbiology, 2024)
High genetic diversity in RNA viruses contributes to their rapid adaptation to environmental stresses, including disinfection. Insufficient disinfection can occur because of the emergence of viruses that are less susceptible to disinfection. However, understanding regarding the mechanisms underlying the alteration of viral susceptibility to disinfectants is limited. Here, we performed an experimental adaptation of murine norovirus (MNV) using chlorine to understand the genetic characteristics of virus populations adapted to chlorine disinfection. Several MNV populations exposed to an initial free chlorine concentration of 50 ppm exhibited reduced susceptibility, particularly after the fifth and tenth passages. A dominant mutation identified using whole-genome sequencing did not explain the reduced susceptibility of the MNV populations to chlorine. Conversely, MNV populations with less susceptibility to chlorine, which appeared under higher chlorine stress, were accompanied by significantly lower synonymous nucleotide diversity (πS) in the major capsid protein (VP1). The nonsynonymous nucleotide diversity (πN) in VP1 in the less-susceptible populations was higher than that in the susceptible populations, although the difference was not significant. Therefore, the ability of MNV populations to adapt to chlorine was associated with the change in nucleotide diversity in VP1, which may lead to viral aggregate formation and reduction in chlorine exposure. Moreover, the appearance of some nonsynonymous mutations can also contribute to the alteration in chlorine susceptibility by influencing the efficiency of viral replication. This study highlights the importance of understanding the genetic characteristics of virus populations under disinfection, which can contribute to the development of effective disinfection strategies and prevent the development of virus populations less susceptible to disinfectants.